2020
DOI: 10.1097/md.0000000000022515
|View full text |Cite
|
Sign up to set email alerts
|

Plum-blossom needle plus Chinese herbal medicine for alopecia areata

Abstract: Background: Alopecia areata (AA) is a common, inflammatory, nonscarring type of hair loss that is characterized by depression, anxiety and social isolation. In recent years, Plum-blossom needle plus Chinese herbal medicine has gradually shown its clinical advantages and been more and more widely used in China. Whereas, there has been no systematic review and meta-analysis. The purpose of this study is to estimate the safety and effectiveness of Plum-blossom needle plus Chinese herbal medicine in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Multiple studies have shown that acupuncture can obtain deqi (qi arrival), by the stimulation of specific points on the body, and even could take the place of drugs, with simple and clean efficiency, broad applicability. [ 19 , 34 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that acupuncture can obtain deqi (qi arrival), by the stimulation of specific points on the body, and even could take the place of drugs, with simple and clean efficiency, broad applicability. [ 19 , 34 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…In connection with the above factors, therapeutic approach of Chinese medicine includes herbal medicine, acupuncture, plum blossom needle and external therapy [19].…”
Section: Management Of Alopecia In Tcmmentioning
confidence: 99%